Statutory placement experiences of final year students on a BSc (Hons) social work program in England. Issue 8 (17th November 2021) - Perry, Emma; Hughes, Samantha
ABSTRACT: Local authority social work departments in England have been facing challenges from a number of different areas for several years. The onset of austerity in 2008 resulted in funding reductions and constraints, many authorities have been deemed to be 'inadequate' or 'in need of improvement' by Ofsted, their inspectorate, and working conditions for practitioners have been found to be poor. It is against this backdrop that social work students on qualifying programs undertake their final year statutory placement. This research investigates the experiences of final year social work students on a BSc (Hons) Social Work program in England. Focus groups and interviews were used to explore the experiences of 18 students placed within both Adults' and Children's Services in three local authorities. Data were analysed thematically and revealed commonalities and differences in experience. Differences between services were apparent with students from Children's Services focusing upon local authority processes whilst Adults' Services gave greater consideration to supervision and support. The areas of motivation and values, awareness of others, power and process also emerged as significant themes.